The exploration analysis of socio economic status of homestay guest in Langkawi and marketing recommendations - Jamaluddin, Askiah; Zainalaluddin, Zumilah; Zulkifli, Zuzafina (Human Resource Management Academic Research Society, 2022)
Homestay business in Langkawi was operated in Malaysia since 1990s. At that time, the Ministry of Tourism, Art and Culture (MOTAC) trained local people as the homestay business owner and provided licensed for homestay operation in Langkawi island area. Generally, this homestay promotes an experience living with homestay business owner and their family, learn the local lifestyle, art and culture. Generally, at that time the consumer segmentation for homestay program is focusing on foreigner and students. Nowadays, the homestay guest is not just get demand from foreigner travelers but mostly the demand from young domestic travelers. The data gathered from LADA shows that the number of domestic travelers to Langkawi Island is increasing year by year. Since the number of homestays are growing in Langkawi, domestic travelers have an opportunity to visit and staying in Langkawi. Therefore, local people in Langkawi should take parts in Langkawi economic development. One of the businesses they could participate is providing the accommodation to travelers, authentic food and nature activities. Furthermore, cooperating with others small business holder who are operating the boat business and island hoping, restaurant, theme parks and farm explorace are the added value in this kind of business. This study aims to analyse the socioeconomic status of homestay guest in Langkawi Island. This result is achieved by two research objectives (1) to identify the socioeconomic background of respondents and (2) to explore the demand of traveling and homestay selection. Thus, this research was conducted using quantitative approach and survey research. There are 364 homestay guests at Langkawi Island involved in this study. The researcher gets co-operations and approval with several homestay business owners. The data was selected by simple random sampling. The findings shows that, most of the homestay guest is a young age group in category 27 to 35 years old. The number of man staying in homestay is higher than women. The young man come with friends and have a nature activities such as fishing, snorkeling and island hoping. Just a little number of man come with family and have a family gathering in Langkawi. In average, the women age 35 and single have an opportunity come to Langkawi with friends. The younger woman may have under tight family protection especially young Malay women. The age of 35 and the single Malay woman may have more freedom than the younger Malay women. They have work, some money and more independent to travel with friends. The little number of solo traveler in this study is a man, they come alone and stay in homestay. Mostly, the homestay guest in this study comes from B40 groups and they stay for one to two nights. The homestay give an opportunity for domestic traveler to come and overnight in Langkawi with payable price. This study is important to LADA and Ministry of Tourism, Act and Culture (MOTAC) to produce a training to local people in Langkawi about accommodation or homestay business. This is to generate the family economics of Langkawi local people. The finding is important for stakeholders and marketers for Langkawi homestay promotion to domestic and foreigner travelers.